Urbanistic Criteria for Planning Privately Owned Public Spaces; Doctoral dissertation [Summary] - Zejnulla Rexhepi (Prostor)
The topic of the doctoral research is privately owned public spaces (POPS). The doctoral research determines the urban criteria (city, district and zone) for the planning of POPS, contributing to theoretical knowledge about their importance at the urban level and highlighting the possibilities and significance of their integral urban planning. The research consists: i. overview theoretical part; ii. the original research part - spatial analysis.